Generation of THz frequency using PANDA ring resonator for THz imaging - Preecha Yupapin; I.S. Amiri; Abdolkarim Afroozeh; None Ali; Preecha Yupapin; Iraj Sadegh Amiri (My University, 2012)
Abstract: In this study, we have generated terahertz (THz) frequency by a novel design of microring resonators for medical applications. The dense wavelength-division multiplexing can be generated and obtained by using a Gaussian pulse propagating within a modified PANDA ring resonator and an add/drop filter system. Our results show that the THz frequency region can be obtained between 40–50 THz. This area of frequency provides a reliable frequency band for THz pulsed imaging. Keywords: THz imaging, THz technology, MRRs, PANDA, add/drop filter
Keywords: Split-ring resonator; Terahertz technology and applications